Prime movers the makers of modern dance in America - Mazo, Joseph H. (Princeton Book Company, Publishers, 2000)
Prime Movers, second edition, is about a group of geniuses who created a new form of art. The art was American modern dance; the early geniuses, while as different from each other in style, background, and influence as ballet from modern dance, were united in purpose. They wanted to create a new theatrical dance form that was serious, unique, and most emphatically not classical ballet. Later modern choreographers made their impact through the clarity and convicti0ons of their own visions